A Neural Adaptive Circular Array for Enhancing SNR and Reducing Interference - Devi, Kavita; Talwar, Rajneesh (International Journal of Computer Sciences and Engineering, 2025)
In today’s mobile communication world, desired as well as interfering signals are mobile. Therefore, a fast tracking system is needed to constantly estimate the directions of those users and then adapt the radiation pattern of the antenna to direct multiple beams to desired users and nulls to sources of interference so that desired users get better quality signal with high SNR and to achieve this Artificial Neural Networks come to rescue to precisely predict which antenna element and the number of antenna elements in circular array to be activated to form better combined radiation pattern to be directed to user.